Electrochemical Polymer Pen Lithography. Issue 28 (10th June 2021) - Oh, EunBi; Golnabi, Rustin; Walker, David A.; Mirkin, Chad A.
Abstract: The development of a massively parallel lithographic technique called electrochemical polymer pen lithography is reported. Pyramidal pen arrays, consisting of more than 10 000 hydrogel pens loaded with metal salts, are integrated into a three‐electrode cell and used to locally reduce ions at each pen tip. This system enables high‐throughput patterning of a variety of metallic inks (e.g., Ni 2+, Pt 2+, Ag + ) on the nanometer to micrometer length scale. By incorporating a z‐direction piezo actuator, the extension length and dwell time can be used to precisely define feature dimensions (210 to 10 µm in width, and up to 900 nm in height, thus far). Furthermore, by controlling the potential and precursor concentrations, more than one element can be simultaneously deposited, creating a new tool for the synthesis of alloy features, such as NiCo, which are relevant for catalysis. Importantly, this methodology enables fine control over feature size and composition in a single pattern, which may make it ultimately useful for rapid, high‐throughput combinatorial screening of metallic features. Abstract : Electrochemical polymer pen lithography (ePPL) is a massively parallel patterning tool for the deposition of metals or metal alloys with size and composition control. ePPL uses a hydrogel array of pyramidal pens for localized electrodeposition, in conjunction with scanning probe lithography and a specialized three‐electrode cell. This versatile technique has potential for high‐throughput 3D printing, biomolecule patterning, or catalyst screening.